Post-Cerebrovascular Stroke and Early Dysphagia Assessment: A Systematic Review - Maniaci, Antonino; Lechien, Jerome R; D'amico, Emanuele; La Mantia, Ignazio; Cancemi, Francesco; Patti, Francesco; Faia, Claudio; Privitera, Elio; Di Luca, Milena; Iannella, Giannicola; Magliulo, Giuseppe; Pace, Annalisa; et al. (Acta Biomedica Atenei Parmensis, 2022)
Purpose: We performed a systematic review on the early assessment of swallowing function after cerebrovascular stroke.Materials and Methods: A systematic review of the English language literature of the past 20 years was performed regarding swallowing function and cerebrovascular stroke. All articles reporting swallowing evaluation through clinical examination validated scores, and diagnostic tools were included in the summary.Results: The systematic review of the literature identified 1,768 potentially relevant studies with 7 papers retrieved with a total of 589 stroke dysphagic patients. While at the clinical neurological assessment, The National Institutes of Health Stroke Scale was more frequently used as a clinical outcome predictor. The Bedside screening approach was carried out in 6 papers to assess patients with probable swallowing disorders. Among the diagnostic tools, seven studies performed the Flexible Fiberoptic Endoscopic evaluation assessing scoring validated system while two papers reported early swallowing outcomes Videofluoroscopic Swallow Study.Conclusions: Our systematic review revealed the findings significantly associated with dysphagia in post-cerebrovascular patients. Endoscopic evaluation of swallowing proved to be the most used method in the literature, effective in identifying early predictors of dysphagia.Given the presence of different assessing scores employed and reduced study samples enrolled, further studies with large courts are necessary for a greater significance.